Developing An Interactive E-Module as Multimodal Learning Strategy in Fostering English Proficiency for High School Students - Islami, Annisa Permata; Eliwarti, Eliwarti; Syarfi, Muhammad (FKIP-Universitas Riau, 2022)
Outdated teaching styles often lead to monotonous English classes in high school and affect students' enthusiasm in the learning process especially if the class is not equipped with technological developments. To address this challenge, this preliminary study designed and developed an interactive e-module with Environmental Context using the Flip Builder application as learning media for Explanation Text material to support English learning through multimodal learning strategies in senior high school. This study employed Research and Development approach and implemented ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as initial research techniques. Moreover, the final evaluation methods occurred to ensure the feasibility of the e-module. The result of this research was an interactive e-module that contains multimodal texts which include written texts, images, animations, videos and games to capture students' interest during the learning process. The validation results indicated that the e-module was valid for all aspects. Therefore, it can be inferred that the interactive e-module using the Flip Builder application on Explanatory Text material with environmental context for high school student was feasible to be implemented in schools.